The Power of Food Vloggers: A Marketing Perspective on Business Growth and Sales Expansion - Bañados, Reamuel R.; Polinar, Mark Anthony N. (Future Science / FSH-PH Publications, 2025)
Social media marketing is a powerful tool for businesses to connect with customers, and one form of this strategy is vlogging, as it offers engaging content that persuades people to try promoted products. This mixed-method research investigates the effectiveness of food vlogging as a social media marketing strategy in improving sales and profitability. Using paired sample t-tests, the study found a significant increase in sales after the adoption of food vlogging, confirming its impact as a sales-driving tool. However, there was no statistically significant improvement in profitability, indicating that increased sales did not directly translate to higher profit margins. Customer feedback revealed that most were persuaded by food vloggers to try featured products, demonstrating strong influencer impact on purchasing decisions. The marketing manager viewed food vlogging positively but emphasized the need for thorough planning and evaluation before implementation. While food vlogging enhances brand visibility and customer reach, businesses must address challenges like inconsistent viewer engagement and high collaboration costs. To maximize return on investment, the study recommends partnering with influencers who match the target audience and focusing on cost-per-action rather than cost-per-view performance metrics.